Program Pemberian Makanan Tambahan dalam Pencegahan Stunting Pada Anak Usia Dini di TK Fathina Majene - St. Maria Ulfah (Institut Agama Islam Negeri Madura, 2024)
This research evaluates the effectiveness of the Supplementary Feeding Program (PMT) in preventing stunting in early childhood at Fathina Majene Kindergarten, Majene Regency, West Sulawesi. This research uses a qualitative approach with a case study design, data was collected through participant observation, in-depth interviews and document analysis. The research results showed that the PMT program at Fathina Majene Kindergarten was effective in improving children's nutritional status, with an average increase in body weight of 10-15% and height of 5-7% after six months of implementation. The risk of stunting was also reduced by 30% in the group of children who participated in the program. This success is influenced by the consistency and quality of additional food, active involvement of teachers and parents, as well as support from local health agencies. In addition, positive changes in children's eating behavior and increased parental nutritional awareness also contributed to the success of the program. In conclusion, the Supplementary Feeding Program at Fathina Majene Kindergarten shows promising potential in improving nutritional status and preventing stunting in early childhood.